Effect of Work Environment and Compensation on Employee Performance in PT Cedefindo Bekasi. - Yohanes Sugiyanta; Matthew Alessandro (LPPM of NAROTAMA UNIVERSITY, 2024)
This study aims to test : (1) Effect of the work environment on employee performance PT PLN (Persero) Generation Implementing Unit Asam Asam. (2) Effect of compensation on employee performance PT Cedefindo Bekasi (3) Effect of work environment and compensation on employee performance PT Cedefindo Bekasi. The design of this research is quantitative research. Populasi penelitian seluruh karyawan PT Cedefindo Bekasi and a sample of 64 respondents. The data was obtained by distributing questionnaires about the work environment and compensation to 64 respondents. This study uses validity and reliability tests to measure validity and reliability, and using the classical assumption test, multiple linear regression analysis, F test, t test and coefficient of deremination (R2). The results of the study show : (1) The work environment has a significant influence on employee performance. (2) Compensation has no significant effect on employee performance. (3) Work environment and compensation together have a significant influence on employee performance.